Cognitive and emotional disorders in university students and teachers: the possibility of treatment with recognan (citicoline) - Nemkova, S A; Semenov, D V; Petrova, E A; Savchenko, D V; Zavadenko, N N; Vozvyshaeva, M Yu; Kanishcheva, A S; Ralleva, A V; Logvinova, E M; Tsvetkov, D A; Charikova, E V; Romanenko, N I; et al. (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2018)
To study the efficacy of recognan (citicoline) in treatment of cognitive, emotional, autonomic, asthenic disorders in university students and teachers. Fifty-eight subjects (17 men and 41 women), mean age 27.75±12.05 years, including who 42 students and 16 teachers were studied. The sample was randomized into 2 groups (29 each): the main sub-group received oral therapy with recognan for 30 days, while the daily dosage was 500 mg (5 ml). In the control group, no drug therapy was performed. Patient's state was assessed with a large battery of psychological tests and psychometric scales. The follow-up period was 30 days. All participants were examined three times (initially, in the middle of the study (day 15), in the end of the study (day 30)). Asthenic state was detected in 69%, autonomic dysfunction in 82.7%, sleep disorders in 75.8% of subjects. A high level of state anxiety was revealed in 22.2%, trait anxiety in 29.8%, a high level of stress was determined in 6,9%. It is shown that the use of recognan (citicoline) has a positive effect on compensation of autonomic and asthenic disorders, improves cognitive status, corrects psycho-emotional disorders, when used as a short (2 week) and month course.